IMPLEMENTASI TATA KELOLA PERUSAHAAN YANG BAIK (GOOD CORPORATE GOVERNANCE) TERHADAP LAPORAN TAHUNAN PERSEROAN TERBUKA (STUDI ANNUAL REPORT 2015 PT.UNILEVER INDONESIA Tbk) - YOHANA APRIYANTI (PREMISE LAW JURNAL, 2017)
This research shows that the implementation of the principle of Good Corporate Governance (GCG) in businesses today is a demand that they will always exist in the global competition. A company which has good transparency report will give positive signal to the market. Disclosure of information in annual report is a significant component in achieving public accountability. Good annual report which implements the principle of GCG in the annual report and meet the regulations can increase its credibility; in turn, it can realize transparency and accountability in managing the company.The research used juridical normative and descriptive analytic method The data were gathered by conducting library research with documentary study and analyzed in the form of sentence, and the conclusion was drawn deductively. The conclusion of the research was that the annual report of 2015 by PT Unilever Indonesia, Tbk had met the principle of GCG.Keywords: Implementation of GCG, Annual Report, Open Corporation